Utilization of Palm oil Plant as a Creative Business in Supporting the Economy: Making Food Plate - Susanti, Melly; Karim, Kurniati; Herfianti, Meiffa; Prima Monique Damarsiwi, Eska; Anas Ahmadi, Edy (International Journal of Psychosocial Rehabilitation, 2020)
The research was conducted with the aim of providing direct insight into the community related to the use of oil palm frond waste as a productive product that has a sale value. The research to be carried out is a descriptive study that illustrates the process and results of the utilization of palm oil waste. The research was carried out by means of simulations of making products and continued to design independently. The method of conducting the research consisted of: (1) field survey; (3) coordination with the village; (4) socialization; (5) simulation; and (6) dissemination of the community response questionnaire. Data collection tools consisted of interview sheets and community response questionnaire sheets. The results showed an increase in public knowledge after being given training in plate making; this result was from holding a plate-making training in the form of plates made from palm fronds.